Analisis Keandalan Unit Hydraulic Power Pack Berbasis Multi-Fluid Scheduled Oil Sampling: Studi Kasus Engine Perkins 6 Silinder di Industri Migas - Muhammad Mukti Ali; Ryan Effendi; Yuni Hermawan; Gaguk Jatisukamto (RESWARA: Jurnal Riset Ilmu Teknik, 2026)
This study aims to analyze the reliability of a Hydraulic Power Pack unit using the Multi-Fluid Scheduled Oil Sampling (SOS) approach by evaluating the condition of engine oil, hydraulic oil, and radiator coolant. The test object is a 6-cylinder Perkins engine with over 10,000 operational hours spanning ±11 years without any history of General Overhaul (GOH). The analysis utilizes laboratory test data from SOS Trakindo Balikpapan, covering parameters such as fuel dilution, viscosity, Total Base Number (TBN), oxidation, wear metals, Particle Quantifier Index (PQI), ISO 4406 cleanliness levels, glycol concentration, nitrite levels, pH, and coolant conductivity. The results indicate that the engine oil has undergone severe degradation, characterized by an extreme fuel dilution of 11.94%, a drastic drop in viscosity to 9.807 cSt, elevated oxidation, and internal wear metal signatures, signaling a decline in lubrication system reliability. Conversely, the hydraulic oil remains within acceptable operational limits despite early-stage particle contamination (ISO Code 20/15). The radiator coolant displays stable physical and chemical properties with 36% glycol concentration, pH 7.4, and a conductivity of 2315 µS/cm, showing no signs of oil cross-contamination. Integrated multi-fluid analysis reveals that the primary degradation mechanism is confined to the engine lubrication system, while the hydraulic and cooling systems maintain operational integrity. This study demonstrates that the Multi-Fluid SOS framework offers a more comprehensive and accurate diagnostic capability for high-operating-hour oil and gas equipment compared to traditional single-fluid monitoring.